A Fast and Rapidly Convergent Iterative Physical Optics Algorithm for Computing the RCS of Open-Ended Cavities - Burkholder, Robert J (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Two major enhancements to the iterative physical optics (IPO) method are described for analyzing the EM scattering from open-ended cavities. First, a Jacobi Minimal Residual (JMRES) iterative algorithm is developed which preserves the physically appealing nature of IPO while establishing robust convergence criteria based on minimizing the residual error. It is shown that the JMRES algorithm usually converges much faster than conjugate gradient based methods for cavities. Second, a form of the fast far field approximation (FaFFA) is implemented to accelerate the computation of the integral operator in IPO. The FaFFA decreases the CPU time by a factor of about 1/5*N[exp(1/3)], where N is the number of surface integration sample points. These improvements allow much larger and more realistically complex cavities to be analyzed with fast IPO.